Short term evaluation of right ventricular function using speckle tracking echocardiography before and after trans-catheter device closure of atrial septal defects in children - Raafat, Omar; Ahmed El-Nawawy; Aly Abdel Mohsen; Hani M. Adel (Acta Biomedica Atenei Parmensis, 2025)
Background: Atrial septal defect (ASD) is a common congenital heart defect (CHD) in children. Evaluating right ventricular (RV) function is essential to understand the impact of ASD and its treatment. Speckle tracking echocardiography (STE) provides a reliable, non-invasive method for detailed RV function assessment. Aims: This study aimed to assess RV function in children with ASD before and after transcatheter device closure using STE. Methods: A case-control study was conducted in the catheterization lab at Smouha Children’s Hospital, University of Alexandria, Egypt. It included 50 children under 18 years with ostium secundum ASD undergoing transcatheter device closure and 50 age-matched controls. Transthoracic echocardiography evaluated RV function through parameters such as RV fractional area change (FAC), myocardial performance index (MPI or Tei index), annular pulsed tissue Doppler imaging (TDI), and tricuspid annular plane systolic excursion (TAPSE). Right ventricular free wall strain (RVFW strain) was measured offline using 2D STE software (TomTec). Results: Significant improvement in RVFW strain was observed following ASD closure, with progressive enhancement at one and three months post-procedure. Parameters such as TAPSE, FAC, and RV MPI also showed improvement, indicating recovery of RV systolic function. Conclusions: ASD is associated with reduced RV contractility and myocardial deformation, primarily due to volume overload. Following transcatheter device closure, RV function improved significantly over time. STE is an effective tool for detecting global and regional myocardial dysfunction and monitoring functional recovery after ASD closure.